Cell cycle kinase polo is controlled by a widespread 3′ untranslated region regulatory sequence in Drosophila melanogaster - Oliveira, Marta S.; Freitas, Jaime; Pinto, Pedro; Jesus, Ana de; Tavares, Joana; Pinho, Mafalda; Domingues, Rita G.; Henriques, Telmo; Lopes, Carla; Conde, Carlos; Sunkel, Claudio E.; Moreira, Alexandra (Molecular and cellular biology, 2019)
Alternative polyadenylation generates transcriptomic diversity, although the physiological impact and regulatory mechanisms involved are still poorly understood. The cell cycle kinase Polo is controlled by alternative polyadenylation in the 3′ untranslated region (3′UTR), with critical physiological consequences. Here, we characterized the molecular mechanisms required for polo alternative polyadenylation. We identified a conserved upstream sequence element (USE) close to the polo proximal poly(A) signal. Transgenic flies without this sequence show incorrect selection of polo poly(A) signals with consequent downregulation of Polo expression levels and insufficient/defective activation of Polo kinetochore targets Mps1 and Aurora B. Deletion of the USE results in abnormal mitoses in neuroblasts, revealing a role for this sequence in vivo. We found that Hephaestus binds to the USE RNA and that hephaestus mutants display defects in polo alternative polyadenylation concomitant with a striking reduction in Polo protein levels, leading to mitotic errors and aneuploidy. Bioinformatic analyses show that the USE is preferentially localized upstream of noncanonical polyadenylation signals in Drosophila melanogaster genes. Taken together, our results revealed the molecular mechanisms involved in polo alternative polyadenylation, with remarkable physiological functions in Polo expression and activity at the kinetochores, and disclosed a new in vivo function for USEs in Drosophila melanogaster.
Gesehen am 21.01.2019